Analysis of Factors Affecting Design Changes in Construction Project with Partial Least Square (PLS). (2015) - Yana, A.A. Gde Agung; Rusdhi H.A.; Wibowo, M. Agung
Abstract: Changes in construction projects are always going to happen and cannot be avoided. Changes causes disruption of performance of construction projects, especially time and cost performance. Many factors can be the cause of changes in construction projects, one of the most influential factor is design change. This study examines the most influential that affect to the design changes in the construction of projects. The influential factors of design changes can be classified into two groups. The internal factors consist of owner, design consultant, construction management consultant, and contractor, while the external factors involve political and economic, the natural environment, advance of technology, and the third-party. The research method employed a questionnaire survey consisting of 31 questions about the occurrence of design changes during the construction of projects, which was distributed to the managers of the construction project. The data was analyzed using Partial Least Square (PLS). The finding shows that the owner is the greatest influential factors on the occurrence of the design changes. The subsequent factors are the design consultant, construction management consultant, political and economic, the natural environment, contractors, third parties, and the advance of technology, which are indicated by the values of the loading factor 0, 884, 0, 859, 0, 846, 0, 771, 0, 577, 0, 523, 0, 328, 0, 255 respectively. This finding can provide useful information for practitioners to reduce the occurrence of design changes on construction of projects, as well as to improve the performance of the construction projects.